Solve for y -6x+3y=24

Math
-6x+3y=24
Add 6x to both sides of the equation.
3y=24+6x
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3y=24+6x by 3.
3y3=243+6×3
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3y3=243+6×3
Divide y by 1.
y=243+6×3
y=243+6×3
Simplify each term.
Tap for more steps…
Divide 24 by 3.
y=8+6×3
Cancel the common factor of 6 and 3.
Tap for more steps…
Factor 3 out of 6x.
y=8+3(2x)3
Cancel the common factors.
Tap for more steps…
Factor 3 out of 3.
y=8+3(2x)3(1)
Cancel the common factor.
y=8+3(2x)3⋅1
Rewrite the expression.
y=8+2×1
Divide 2x by 1.
y=8+2x
y=8+2x
y=8+2x
y=8+2x
y=8+2x
Solve for y -6x+3y=24

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top